THE INFLUENCE OF LEADERSHIP AND FINANCIAL COMPENSATION ON EMPLOYEE PERFORMANCE WITH WORK ENVIRONMENT AS A MEDIATING VARIABLE AT THE PANDEGLANG REGIONAL REVENUE OFFICE - Supriatih, Ratih; Rustandi, Tata; Permana, Angrian (Yayasan Education and Social Center, 2025)
The purpose of this study is to identify the direct and indirect effects of these variables on employee performance through the work environment. The method used is Structural Equation Modeling - Partial Least Squares (SEM-PLS) with a quantitative approach, involving 90 respondents from 97 ASN population. The results showed that leadership has a positive and significant influence on the work environment (β=0.310; t=2.904; p=0.004), and affects employee performance (β=0.287; t=3.186; p=0.002). Financial compensation has a significant positive effect on the work environment (β=0.664; t=6.442; p=0.000), and affects employee performance (β=0.271; t=2.226; p=0.026). The work environment itself has a positive and significant influence on work productivity (β=0.432; t=3.559; p=0.000). In addition, leadership and incentives have a significant effect on employee performance through the work environment, with coefficient values β = 0.134 (t=2.124; p=0.034) and β = 0.286 (t=3.270; p=0.001).This research provides important insights for improving the performance of ASN employees of the Regional Revenue Agency (DISPENDA) of Pandeglang Regency by emphasizing the importance of humanist leadership, increasing financial compensation and making the work environment better. These strategies can create more productive employee performance.